Finite nonabelian p-groups of exponent >p with a small number of maximal Abelian subgroups of exponent >p - Janko, Zvonimir (Glasnik matematički, 2017)
Y. Berkovich has proposed to classify nonabelian finite p-groups G of exponent >p which have exactly p maximal abelian subgroups of exponent >p and this was done here in Theorem 1 for p=2 and in Theorem 2 for p>2. The next critical case, where G has exactly p+1 maximal abelian subgroups of exponent >p was done only for the case p=2 in Theorem 3.
Gesehen am 22.02.2018